Food Processing and Packaging Technologies Recent Advances - Shankar Tumuluru, Jaya (IntechOpen, 2023)
Food processing, preservation, and packaging is a highly interdisciplinary science. Various techniques and technologies have been developed to extend food shelf life, minimize the risk of contamination, protect the environment, and improve foods' functional, sensory, and nutritional properties. Some of the many benefits of food processing, preservation, and packaging include increased food safety, improved nutrition, longer shelf life, and increased economic opportunities. In addition, food processing and preservation help to reduce post-harvest losses. Developing novel food processing, preservation, and packaging technologies is critical to preserving food quality, improving sensory characteristics, and reducing losses. At present, there is a great emphasis on developing novel biobased and intelligent packaging technologies that are safe for food and reduce environmental pollution. This book provides a comprehensive overview of food processing and preservation packaging to tackle the challenges of food safety, nutritional security, and sustainability. Chapters address such topics as edible packaging materials, intelligent packaging materials, nanotechnology for enhancing the shelf life of food products, advanced food packaging systems, green materials for food packaging, antimicrobial packaging materials, food drying technologies, methods of food processing, food analysis using acoustic and thermal methods, food formulations, and functional foods. This volume is a useful resource for students, researchers, and food processing preservation professionals. It highlights advances in food processing and packaging systems to increase food quality and preserve food longer without generating waste.